Role of nanostructure in the behaviour of BiVO4–TiO2 nanotube photoanodes for solar water splitting in relation to operational conditions - Perini, João Angelo Lima [UNESP]; Tavella, Francesco; Ferreira Neto, Elias Paiva [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Giusi, Daniele; Centi, Gabriele; Perathoner, Siglinda; Ampelli, Claudio (Elsevier, 2021)
BiVO4 nanoparticles deposited onto TiO2 nanotube arrays (TNT) are used as heterostructured photoanodes in a compact-design photo-electrocatalytic (PEC) cell for solar-driven water splitting. No dopants, photosensitizers or other cocatalysts are added to enhance the catalytic activity but attention is focused on the relationship between TNT nanostructure (necessary for the novel compact-design PEC cell) and method of BiVO4 deposition. Three indicators are used to evaluate the catalytic performances: i) photocurrent density, ii) H2 production rate, and iii) solar-to-hydrogen efficiency (STH). Their dependence on photoanode characteristics (i.e. grade of TNT crystallinity) and operational parameters, such as anolyte concentration (NaOH in the range 0.1–1.0 M) and type of solar illumination (open spectrum or AM 1.5G filtered light), is analysed. While a linear relationship is observed between H2 production rate and photocurrent density, the behaviour of STH efficiency is more complex. An ordered and crystalline TNT film is necessary to maximize photocurrent density and H2 production rate, which can be further enhanced by depositing BiVO4. However, the methodology of BiVO4 deposition and the specific TNT nanoarchitecture have a marked influence in terms of light absorption, electronic conductivity and rate of reaction between photogenerated holes and OH−. This leads to an improvement or a depression of the photocatalytic behaviour as BiVO4 may in some cases favour charge recombination. Thus, understanding the role of the photoelectrodes in relation to the operational conditions may favour the preparation of scalable electrodes for improving performances of PEC cells in the generation of solar fuels.
Keywords: Bismuth vanadate; H2 production; Nanoheterojunction; Photo-electrocatalysis (PEC); TiO2 nanotubes; Water splitting